2018
DOI: 10.1097/lgt.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Beliefs and Prevalence of LSIL/HSIL Among a University-Based Population in Cameroon

Abstract: Objective The aim of the study was to determine beliefs and utilization of cervical cancer screening and prevalence of low-grade squamous intraepithelial lesion/high-grade squamous intraepithelial lesion among a university-based population in the Southwest region of Cameroon. Materials and Methods A public-private partnership was established between the University of Arizona, University of Buea, and the Cameroon Baptist Convention Health Services. A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Similar to prior studies, 25,27,28 women in our study reported mild pain, and some participants reported cramping and feelings of fainting. No serious side effects were reported, consistent with prior findings 27,29‐33 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to prior studies, 25,27,28 women in our study reported mild pain, and some participants reported cramping and feelings of fainting. No serious side effects were reported, consistent with prior findings 27,29‐33 …”
Section: Discussionsupporting
confidence: 89%
“…No serious side effects were reported, consistent with prior findings. 27,[29][30][31][32][33] However, when asked if recovery following treatment was an issue, over a third of women reported that it was an issue due to reasons such as vaginal discharge, bleeding and pain. Other studies 25,27,28 have found that some women report discharge, pain or bleeding shortly after treatment with thermal ablation, but none have assessed whether women find these symptoms to be problematic throughout recovery.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 1336 were uploaded to Covidence for abstract and title screening. Two independent reviewers identified 64 papers for full text evaluation of which 12 were found to meet all inclusion criteria for this review 9–11 18–26. Of note, 30 papers were identified as abstracts from conference proceedings with no full text available at that time.…”
Section: Resultsmentioning
confidence: 99%
“…The paper reporting on the largest study population was included in the meta-synthesis 12. A subset of four studies that provided narrative results alone for a composite measure of all side effects were excluded from meta-synthesis due to concerns around reporting bias 23–26. Study inclusion and reasons for exclusion at full text review are provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses diagram (online supplemental figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Screening is done during sporadic campaigns or through medical prescriptions. Few studies found a screening rate between 31-32,5% in Cameroon [7,8]. Meanwhile, effective screening rate is low.…”
Section: Introductionmentioning
confidence: 99%